Determinants of Private Capital Flows in the 1970's and 1990's : Is there Evidence of Contagion? - Valdes, Rodrigo (IMF Working Papers; Working Paper ;, 2001)
This paper studies the determinants of private capital flows to developing countries during the last two episodes of large inflows, the late 1970s-early 1980s and the 1990s. The paper also tests for contagion effects in capital flows among recipient countries, and tries to identify specific channels through which such effects can occur. It tests for neighborhood effects, trade-related effects, and for contagion based on the countries having similar macroeconomic indicators. The results show strong evidence for the first two effects during the 1990s, and indicate that the third effect varies depending on the type of capital flow.